Mystifying, Mysterious Michael Corder's return to Covent Garden - Simpson, Jane 1927-2008 (Dance Books Ltd., Alton,Hampshire (UK), 2008)
Michael Corder's returns to Convent Garden and said: "It's no fault of their that the new cast can't just step into the custom-made shoes of their predecessors." "This must be the glummest, most tragedy-ridden season the Royal Ballet has ever offered us."